Dementia Friendly Manhattan - Biggins, Anna (My University, 2022)
Overall, the survey confirmed a low awareness of the concept of dementia friendly communities among Riley County adults (17.2%). However, after reading a brief description of the purpose and goals of dementia friendly communities, respondents indicated a high level of support for exploring this initiative in Manhattan (86.53% “in favor” and 12.44% “maybe”). While respondents overwhelmingly thought that the initiative would be advantageous to the community (68% indicated high levels of perceived relative advantage), the majority of respondents also thought it would be a complex task to undertake (63.5% indicated high levels of perceived complexity). These results were communicated to the FHWC at a regular Coalition meeting and indicated that the Dementia Friendly Manhattan initiative would be a worthwhile pursuit of the Coalition. Thus, the survey results were used to identify the priorities for beginning the Dementia Friendly Manhattan initiative.
Keywords: Dementia; Public Health; Riley County Kansas